The relationship between internal audit characteristic, audit committee characteristic and interaction between internal audit and audit committee on internal audit contribution / Hasnah Haron and Tong Chue Qun. - haron, Hasnah; Tong, Chue Qun (Universiti Teknologi MARA Selangor, 2016)
Internal auditing has becomes as an important tool in helping an organisation to achieve its objectives. Organisations with internal audit activities capable to identify business risks, and system inefficiencies and ineffectiveness, take appropriate corrective actions, and ultimately support continuous improvement. Therefore, its contribution must be monitored in order to maintain and enhance the credibility of internal audit. The objectives of this study are, therefore, to investigate the contribution of internal audit and its determinants of internal audit characteristics, audit committee characteristics, and interaction between internal audit and audit committee. Questionnaires were distributed to 413 public listed companies in Bursa Malaysia and 172 responses were received. The finding showed that internal audit contributed the most in internal control. The result revealed that internal audit competence has a significant effect on internal contribution. Hence, internal audit team should consist of member with different expertise; both in technical and soft skills. Factors related to audit committee and interaction between audit committee and internal audit were not found to be significant. The relationship between audit committee and internal audit needs to be reinforced for better oversight mechanism. The Malaysian Code of Corporate Governance (MCCG) and the International Professional Practice Framework (IPPF) should require higher compliance to IPPF with the disclosure on the audit committee activities.